2021
DOI: 10.5380/ce.v26i0.74702
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies and Quality of Life Among Older People With Hypertension: A Cross-Sectional Study

Abstract: Objetivo: analisar as diferenças nos mecanismos de enfrentamento e na qualidade de vida entre idosos com hipertensão em casas de repouso da Indonésia. Método: foi realizado um estudo transversal entre 71 idosos durante dezembro de 2018 em casas de repouso. Foi utilizado um questionário autoadministrado foi para identificar as características dos participantes e a qualidade de vida dos idosos, ao mesmo tempo em que o esfigmomanômetro foi usado para medir a pressão arterial. A análise de dados foi feita com test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
0
0
1
Order By: Relevance
“…In line with this study, it was found that there was a positive relationship between the emotional focus of coping and coping with social support which had a major impact on the lives of elderly caregivers [22]. The study proves that there is a positive influence between coping strategies and the quality of life of the elderly, other research also states that [40]. Coping strategies used in this study were acceptance, religious approach, emotional support and positive reflaming.…”
Section: Int J Publicsupporting
confidence: 84%
“…In line with this study, it was found that there was a positive relationship between the emotional focus of coping and coping with social support which had a major impact on the lives of elderly caregivers [22]. The study proves that there is a positive influence between coping strategies and the quality of life of the elderly, other research also states that [40]. Coping strategies used in this study were acceptance, religious approach, emotional support and positive reflaming.…”
Section: Int J Publicsupporting
confidence: 84%
“…Hipertensi dan diabetes melitus menyebabkan dampak fisik dan kesehatan mental bagi penderitanya. Seseorang yang menderita hipertensi memiliki kualitas hidup yang lebih rendah berkaitan dengan fungisonalitas fisik, kesehatan secara umum, vitalitas, dan fungsi sosial (Mardiana et al, 2021;Xu et al, 2016). Diabetes melitus juga menyebabkan penurunan kualitas hidup pada penderitanya ketika komplikasi mulai berkembang atau disertai dengan penyakit penyerta (Trikkalinou et al, 2017) depresi pada penderita penyakit kronis berhubungan signifikan dengan persepsi mereka terhadap pengendalian penyakit kronis (Alkhathami et al, 2017).…”
Section: Pendahuluanunclassified